Funding Civil Justice in Scotland: Full Cost Recovery, at What Cost to Justice?. Issue 1 (January 2020) - Christman, Ben; Combe, Malcolm
Abstract : In Scotland, there has been an increasing trend for the costs associated with the administration of civil justice to be met by the users of the court system. Such a policy can broadly be referred to as "full cost recovery". A recent Scottish Government consultation on court fees uncritically continued with this overall approach, but various consultees nevertheless took the opportunity to critique full cost recovery in the context of that consultation and more generally. This article takes up that analysis, in a manner that should also be of interest to non-Scottish readers who may be contending with a similar challenge in another jurisdiction, by critiquing full cost recovery in principle and by offering potential routes by which its implementation might be challenged. It begins by explaining what full cost recovery actually is and investigating its origins, before interrogating some of the assumptions or acquiescence that seems to have developed around the issue and discussing the potential for litigation against court fees in Scotland.